ANALYSIS OF THE EFFECTIVENESS OF THE INFLUENCE OF THE BAITULMAAL MUAMALAT EMPOWERMENT PROGRAM "SAHABAT UMKM INDONESIA" ON THE EXISTENCE OF MSME PERFORMANCE WITH INTRINSIC MOTIVATION AS A MEDIATING VARIABLE - Nurlela, Nurlela; Nurhidayati, Nurhidayati; Putra, Bayu Purnama (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study analyzes the effectiveness of Baitulmaal Muamalat’s "Sahabat MSME Indonesia" empowerment program on MSME performance, with intrinsic motivation as a mediating variable. Using a quantitative approach with 80 respondents and SmartPLS-SEM, the results reveal that training significantly affects intrinsic motivation and MSME performance. Mentoring significantly influences MSME performance but not through intrinsic motivation. Intrinsic motivation itself has a significant positive impact on MSME performance. Nearly 65% of respondents had a high school or university degree, suggesting that training was sufficient for understanding the material. However, mentoring appeared more focused on fulfilling schedules, with solutions less relevant to MSME needs, thereby limiting its influence on intrinsic motivation. This study is limited by its quantitative design and reliance on a single institution. Future studies could combine quantitative and qualitative methods to improve the robustness and generalizability of the findings.